DC Motor Speed Control System with PWM (Pulse Width Modulation) Technique Based on Arduino For Centrifugation Equipment Application - Ellen Margirahayu; Junaidi Junaidi; Gurum Ahmad Pauzi; Sri Wahyu Suciyati (Journal of Energy, Material, and Instrumentation Technology, 2022)
A DC motor speed control system with Arduino-based PWM (Pulse Width Modulation) technique has been realized for centrifugation applications. Tool design consists of hardware and software. The hardware used is Arduino Uno, brushless DC motor, ESC (electronic speed control), optocoupler, 4x4 keypad, and seven-segment, and the software used is Arduino IDE. The working principle of this tool is that Arduino will process input from the keypad and provide a signal to the ESC (electronic speed control) to drive a brushless DC motor. The optocoupler sensor will detect motor rotation, and the data obtained will be displayed on the seven segments. This tool works with a speed range of 4,000 to 7,000 RPM. Rotational speed testing has been carried out using the DT-2234C+ tachometer. The test results show the highest error occurs at a speed of 5,000 RPM which is 3.62% and the lowest error occurs at a speed of 6,000 RPM at 1.01%.